1994
DOI: 10.1007/bf00136362
|View full text |Cite
|
Sign up to set email alerts
|

Hexacyanoferrate(III) oxidation of n-valeric and iso-valeric acid hydrazides in perchloric acid

Abstract: The kinetics of the title reaction were determined spectrophotometrically. The oxidation was second order; but first order with respect to both [hexacyanoferrate(III)]o and [hydrazide]0. The effect of [HCIO4] on the reaction rate was curious; as the HC10 4 concentration increased the rate decreased and, reaching a minimum. The rate was slightly enhanced by an increase in ionic strength, but was insensitive to added salts, such as NaC10~, NaNO3, NaC1, KC1, LiC1 and K4Fe(CN)6 at constant ionic strength. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…When we first began this work little was known about the mechanism for the oxidation of hydrazides although it was well established that an electrophilic species is generated that has been exploited for acyl nucleophilic substitution reactions. 6,7 Only recently, when Braslau oxidized aryl and aliphatic hydrazides with PbO 2 in the presence of the radical trap 2,2,6,6,tetramethylpiperidine-1-oxyl (TEMPO, 3, Fig. 1), was it shown that the oxidation of hydrazides with transition metal oxidants involves the formation of an acyl radical intermediate.…”
mentioning
confidence: 99%
“…When we first began this work little was known about the mechanism for the oxidation of hydrazides although it was well established that an electrophilic species is generated that has been exploited for acyl nucleophilic substitution reactions. 6,7 Only recently, when Braslau oxidized aryl and aliphatic hydrazides with PbO 2 in the presence of the radical trap 2,2,6,6,tetramethylpiperidine-1-oxyl (TEMPO, 3, Fig. 1), was it shown that the oxidation of hydrazides with transition metal oxidants involves the formation of an acyl radical intermediate.…”
mentioning
confidence: 99%